2022
DOI: 10.1021/acsomega.2c03800
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Slurry Erosion and Corrosion Resistance of Plasma-Sprayed Fly Ash Coatings for Marine Applications

Abstract: Fly ash (FA), a multicompound mineral, is an industrial waste produced during coal burning in thermal power stations. It has been regarded as the most environmentally hazardous material. Furthermore, handling FA has been a significant challenge for many developing countries. Therefore, researchers have been exhorted to enhance its usage to counter its handling issues. FA is enriched with mullite, silica, and alumina. Having such mineralogy, FA can be envisaged as a promising candidate for combating erosion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Prior to deposition, the work surface (30 mm × 25 mm) of the substrate was sandblasted and roughened and then immersed in acetone solution for ultrasonic cleaning for 20 min. To ensure a high bond strength and long service life, , the thickness of both coatings was controlled at about 300–310 μm, and their optimum spraying parameters are provided in Table S4. Subsequently, the coatings were polished to mirror surface ( R a ≤ 0.1 μm) with SiC sandpapers (800–2000 meshes) and water-borne diamond paste with a 0.5 μm particle size.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to deposition, the work surface (30 mm × 25 mm) of the substrate was sandblasted and roughened and then immersed in acetone solution for ultrasonic cleaning for 20 min. To ensure a high bond strength and long service life, , the thickness of both coatings was controlled at about 300–310 μm, and their optimum spraying parameters are provided in Table S4. Subsequently, the coatings were polished to mirror surface ( R a ≤ 0.1 μm) with SiC sandpapers (800–2000 meshes) and water-borne diamond paste with a 0.5 μm particle size.…”
Section: Methodsmentioning
confidence: 99%
“…Before deposition of the HA coatings, the 50 × 25 × 4 mm Ti-6Al-4V substrates were grit blasted using a hot grit blaster (GB-02 HVAF blast feeder supplied by Kermetico, Inc.), and HA was deposited by following the parameters of Table . The substrate was preheated to ∼200 °C to remove moisture and roughened , before depositing, and the substrates were cleaned with acetone before and after grit blasting. Surfaces were grit blasted using alumina grits for around 2–3 min.…”
Section: Methodsmentioning
confidence: 99%
“…Mostly cenosphere and glass microballoon (GMB) are used as the reinforcement in developing syntactic foams (Patil et al , 2019; Bharath et al , 2021b). These fillers are not only used in developing syntactic foams but also in wide variety of industries, for example, cenospheres are used in applications like thermal barrier coatings (Chavana and Bhajantri, 2022). Previous studies on GMB-based foams have shown that these syntactic foams have a good weight reduction potential, strength-to-weight ratio and low moisture absorption (Doddamani et al , 2015; Bharath et al , 2020a; Nikhil, 2007).…”
Section: Introductionmentioning
confidence: 99%